STANDARISASI MARKA APRON GUNA MENJAMIN KESELAMATAN PERGERAKAN KENDARAAN GROUND SUPPORT EQUIPMENT (GSE) DI BANDAR UDARA INTERNASIONAL SULTAN AJI MUHAMMAD SULAIMAN SEPINGGAN BALIKPAPAN - Citra Rahayu Hidarwanti; Arnaz Olieve; Kusno (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Sultan Aji Muhammad Sulaiman Sepinggan Balikpapan Airport is an airport that is the main gateway for air transportation in East Kalimantan. This airport always experiences an increase in the number of flights every year. The increasing number of flights is also accompanied by an increase in aircraft ground support equipment, namely Ground Support Equipment (GSE) vehicles. Therefore, it is necessary to have markings that are in accordance with the standards in aviation regulations to facilitate the operation of GSE vehicles when carrying out ground service aircraft on the apron. The research in this final project discusses the problem of markings at SAMS Sepinggan Airport Balikpapan that do not meet the aviation regulatory standards, where there are still many GSE vehicles parked in any place, the absence of Equipment Parking Area (EPA) markings, as well as some markings that are still overlapping and has started to fade. The main reference used in this research is the Regulation of the Director General of Civil Aviation Number 326 of 2019 concerning technical and operational standards of civil aviation safety regulations-section 139 related to the standardization of markings on the apron. The data collection method used in this research is descriptive qualitative research method by collecting data through observation, interviews, literature study, and documentation. The results of this study can be concluded that the arrangement of GSE vehicle placement needs to be improved again and the presence of three storages is considered sufficient to accommodate GSE vehicles that will or have been operating as a short-term solution, while the long-term solution is to procure and rejuvenate all airborne markings, especially in the apron area of an airport.